Pulse oximeter as a home assessment tool: Knowledge and user experience among the community in Malaysia during the COVID-19 pandemic - Siew-Keah Lee; Jin Wei Ma; Khai Ying Chan; Yi Song Cheong; Wan Ting Hong; Regine Chew Yi Ong; Wei Cheng Tay; Ang-Lim Chua (Asian Pacific Journal of Tropical Medicine, 2022)
Objective: To determine the degree of knowledge in the usage of pulse oximeter as a home assessment tool among the community in Malaysia. Methods: A cross-sectional survey was conducted in November 2021. The questionnaire assessed the knowledge in using pulse oximeters, user experience and opinions in using pulse oximeter as a home assessment tool during the pandemic. Results: A total of 504 respondents were included in the study, and the mean score in knowledge related to application of pulse oximetry was 73.00%, while the mean score in knowledge related to factors affecting pulse oximetry readings was only 38.51%. A total of 90.5% of the respondents recognised normal pulse rate and 88.5% knew the blood oxygen saturation levels of a healthy adult, while 69.4% recognised the definition of silent hypoxia. In addition, the majority of the respondents agreed that factors such as poor blood circulation (71.2%), excessive movements (69.8%), and hand position (60.7%) affected oximetry readings. However, 61.7%, 81.7%, 77.2% and 76.8% of the respondents could not identify nail polish, skin colour, skin thickness and tattoos as factors that may affect oximetry readings respectively. Conclusions: The respondents showed a satisfactory level of knowledge related to application of pulse oximetry, but a poor level of knowledge related to factors affecting pulse oximetry readings among the community in Malaysia. Continuous efforts in educating the community on the correct use of pulse oximeters are crucial for appropriate home assessment and avoiding unnecessary stress.